Organic positive electrode material of aluminum ion battery and aluminum ion battery

Through the porous structure of covalent organic frame materials and the π-π conjugated frame design, the problems of high solubility and poor cycle stability of the positive electrode material of aluminum ion battery are solved, and the battery performance of high capacity and fast charging and discharge are achieved.

CN120413666APending Publication Date: 2025-08-01XUANCHENG VOCATIONAL & TECH COLLEGE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510468295.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-15
Publication Date
2025-08-01

AI Technical Summary

Technical Problem

The existing aluminum ion battery positive electrode materials have problems such as high solubility, low utilization of active sites, poor circulation stability, low overall energy density of the battery and insufficient rate performance.

Method used

The covalent organic frame material is used as organic active substances to synthesize the porous π-π conjugated skeleton with a porous structure through solvothermal method, including carbonyl active sites, combined with conductive agents and binders, and prepare the positive electrode material of aluminum ion battery, providing rich active sites and fast conductivity channels to inhibit dissolution and volume expansion.

Benefits of technology

It has achieved high specific capacity, fast charging and discharging capabilities, excellent cycle stability and temperature adaptability. The capacity retention rate exceeds 93.6% after 6,000 cycles, and the battery performance is significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120413666A_ABST
    Figure CN120413666A_ABST
Patent Text Reader

Abstract

The invention discloses an aluminum ion battery organic positive electrode material and an aluminum ion battery, and the aluminum ion battery organic positive electrode material comprises the following components: an organic active substance which is a covalent organic framework material synthesized by 1, 3, 5-tri (4-formylphenyl) benzene (TFP) and a quinone compound with carbonyl active sites through a solvothermal method, the covalent organic framework material has a porous structure and a pi-pi conjugated skeleton. The covalent organic framework material is used as an organic active substance, the covalent organic framework material has rich carbonyl active sites, carbonyl can be disconnected and coordinated with AlCl2 < + > in the electrolyte in the discharging process, the previous state can be reversibly recovered in the charging process, and therefore the reversible capacity per gram is high. AlCl2 < + > can be rapidly diffused in the positive electrode due to a strong pi-pi conjugated skeleton and a porous structure, so that the positive electrode has rapid charging and discharging capability. The framework structure has low solubility and a more stable structure, so that the material has excellent cycling stability and excellent temperature adaptability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electrochemical energy storage technology, and in particular to an organic positive electrode material for an aluminum ion battery and an aluminum ion battery. Background Art

[0002] Rechargeable aluminum-ion batteries have attracted increasing attention due to their abundant resources, high volume / mass specific capacity and high safety. However, due to the high surface charge density of trivalent aluminum ions, strong Coulomb repulsion often occurs between them and the host material. Some traditional inorganic cathode materials (such as V2O5] and Mo6S8) undergo structural collapse during repeated cycles, which leads to rapid degradation of battery capacity. In addition, although the theoretical specific capacity of sulfur-based cathodes based on conversion reactions is as high as 1,672 mAh g -1 However, the oxidation kinetics of aluminum polysulfide are slow and the reversibility of the electrochemical reaction is poor, which leads to a rapid decline in the cycle stability of the battery. Organic materials are considered to be highly promising energy storage materials due to their structural design, low cost, and environmental protection. Compared with inorganic materials, organic matter does not contain heavy metals. After the battery is retired, whether it is recycled or incinerated, it will not cause much pollution to the environment. At the same time, compared with the rigid crystal structure of inorganic materials, its flexible structure is very conducive to AlCl4 - 、AlCl2 + and AlCl 2+ At present, some organic materials have been used in the research of aluminum ion batteries, but most of them still face problems such as poor cycle stability, low capacity, and poor rate performance.

[0003] Therefore, it is necessary to provide an organic positive electrode material for an aluminum ion battery and an aluminum ion battery. Summary of the Invention

[0004] This application addresses the problems of existing aluminum ion battery positive electrode materials such as high solubility, low active site utilization, poor cycle stability, low overall battery energy density, and insufficient rate performance, and provides an organic positive electrode material for aluminum ion batteries and an aluminum ion battery.

[0005] In a first aspect, the present application provides an organic cathode material for an aluminum ion battery, comprising the following components, calculated by weight:

[0006] Organic active material, the organic active material is a covalent organic framework material synthesized by a solvent thermal method from 1,3,5-tris(4-formylphenyl)benzene (TFP) and quinone compounds with carbonyl active sites. The covalent organic framework material has a porous structure and a π-π conjugated skeleton.

[0007] This application uses covalent organic framework materials as organic active substances, which have abundant carbonyl active sites. During the discharging process, the carbonyl groups will break and coordinate with AlCl2 in the electrolyte + and will reversibly return to the previous state during charging. Therefore, this covalent organic framework material has a relatively high reversible specific capacity. Its strong π-π conjugate skeleton and porous structure enable AlCl2 + to rapidly diffuse in the positive electrode, endowing it with fast charge and discharge capabilities. The framework structure has low solubility and a more stable structure, making it have excellent cycle stability and good temperature adaptability. Among them, a rigid planar monomer TFP and a quinone compound (such as 2,6-diaminoanthraquinone) are used to construct an imine bond covalent skeleton through a Schiff base reaction, and ordered growth is guided by slow condensation and π-π stacking under solvothermal conditions to form a layered stack; solvent molecules act as soft templates to dynamically regulate the mesopore size, and finally a crystalline porous framework with a high specific surface area and high stability is obtained. The covalent organic framework material not only provides abundant active sites (such as carbonyl / amino groups) to achieve high capacity, but also promotes rapid electron conduction through the π-π conjugate skeleton. The strong covalent bond network and rigid pore structure effectively inhibit dissolution and volume expansion, and the capacity retention rate is >93.6% after 6,000 cycles.

[0008] Furthermore, the X-ray diffraction pattern of the covalent organic framework material has a diffraction peak at 2θ < 5°. This indicates that the covalent organic framework material is a π-π layered stack, and the ordered pores provide a rapid transmission channel for AlCl2 +

[0009] Furthermore, the quinone compound is at least one of 2,6-diaminoanthraquinone, 2,7-diamino-9,10-phenanthrenequinone, and 2,7-diaminopyrene-4,5,9,10-tetrone. Quinone compounds containing amino and carbonyl groups such as 2,6-diaminoanthraquinone (DAAQ) and 2,7-diamino-9,10-phenanthrenequinone (DAPQ) are selected to form reversible coordination with AlCl2+ through dual redox active sites (-NH2 and -C=O) to improve the capacity; the large conjugated planar structure of phenanthrenequinone increases the discharge voltage plateau (comparing Examples 1 and 2), indicating that molecular extended conjugation can optimize the redox potential.

[0010] Furthermore, it contains 40 - 70 parts of organic active substances and 28 - 62 parts of inactive components. If the proportion of organic active substances is too high, it may lead to a decrease in ionic conductivity and cycle stability; if the proportion of organic active substances is too low, the capacity density will decrease.

[0011] Furthermore, it contains 20 - 50 parts of conductive agent and 8 - 12 parts of binder.

[0012] ​Further, the conductive agent is selected from at least one of conductive carbon black, Ketjen black, graphene, acetylene black, and carbon nanotubes.

[0013] Further, the binder is selected from at least one of polyvinylidene fluoride, sodium carboxymethyl cellulose, sodium alginate, and styrene-butadiene rubber. The binder can provide strong adhesion, inhibit the volume expansion of the covalent organic framework material particles during charge and discharge, reduce the swelling degree of the binder in the ionic liquid, and avoid the destruction of the electrode structure.

[0014] Further, the specific surface area of the above-mentioned organic cathode material is greater than 300 m 2 / g.

[0015] The second aspect of the present application provides an aluminum-ion battery based on the above-mentioned aluminum-ion battery cathode material, including:

[0016] a) A positive electrode, which is prepared by coating the organic cathode material according to any one of claims 1-6 on a conductive current collector;

[0017] b) A negative electrode, which is a metal foil;

[0018] c) A separator, which is an insulating material separator;

[0019] d) An electrolyte.

[0020] The above-mentioned aluminum-ion battery has excellent cycle stability and temperature adaptability.

[0021] Further, the preparation method of the positive electrode includes the following steps:

[0022] a) Mix the organic active material, conductive agent, and binder according to the mass fraction, add a solvent and stir until the slurry is uniform;

[0023] b) Coat the slurry on the surface of the current collector and dry it under vacuum at 60-80 °C;

[0024] c) Cut the dried electrode sheet into a preset size.

[0025] Further, the electrolyte is a room-temperature ionic liquid composed of anhydrous AlCl3 and 1-ethyl-3-methylimidazolium chloride in a molar ratio of 1.2-1.5:1. When the molar ratio of AlCl3 to the ionic liquid is 1.2-1.5:1, the viscosity of the electrolyte is relatively low, which is beneficial to the migration of Al 3+ ions. Description of the Drawings

[0026] Figure 1 Cyclic voltammetry curves of DAAQ-COF at different scanning rates in Example 1 according to the present application

[0027] Figure 2Cyclic voltammetry curves of DAAQ-COF at different current densities in Example 1 according to the present application

[0028] Figure 3 Cyclic performance graph of DAAQ-COF in Example 1 according to the present application

[0029] Figure 4 Cyclic voltammetry curves of DAPQ-COF at different scan rates in Example 2 according to the present application

[0030] Figure 5 Cyclic voltammetry curves of DAPQ-COF at different current densities in Example 2 according to the present application

[0031] Figure 6 Cyclic performance graph of DAPQ-COF in Example 2 according to the present application.

[0032] Figure 7 N2 adsorption curve of DAPQ-COF in Example 1 according to the present application

[0033] Figure 8 N2 adsorption curve of DAPQ-COF in Example 2 according to the present application Detailed implementation manners

[0034] To facilitate the understanding of the present application, the present application will be described more comprehensively below. The present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, these embodiments are provided to make the understanding of the disclosure of the present application more thorough and comprehensive.

[0035] In addition, the terms "first" and "second" are only used for descriptive purposes and cannot be understood as indicating or implying relative importance or implicitly specifying the quantity of the indicated technical features. Thus, the features defined with "first" and "second" may explicitly or implicitly include at least one of such features. In the description of the application, the meaning of "a plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined. In the description of the present application, the meaning of "several" is at least one, such as one, two, etc., unless otherwise clearly and specifically defined.

[0036] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those of ordinary skill in the technical field to which the present application belongs. The terms used in the description of the present application in this specification are only for the purpose of describing specific embodiments and are not intended to limit the present application. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.

[0037] In this application, among the technical features described in an open-ended manner, it includes a closed technical solution composed of the listed features, as well as an open technical solution including the listed features.

[0038] In this application, regarding numerical ranges, unless otherwise specified, the above numerical ranges are considered continuous and include the minimum and maximum values of the range, as well as each value between such minimum and maximum values. Further, when the range refers to integers, it includes each integer between the minimum and maximum values of the range. In addition, when multiple ranges are provided to describe features or characteristics, these ranges can be combined. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all sub-ranges subsumed therein.

[0039] In this application, for the percentage content involved, unless otherwise specified, for solid-liquid mixtures and solid-solid mixtures, it refers to the mass percentage, and for liquid-liquid mixtures, it refers to the volume percentage.

[0040] In this application, for the percentage concentration involved, unless otherwise specified, it all refers to the final concentration. The final concentration refers to the proportion of the added component in the system after adding this component.

[0041] For the temperature parameters in this application, unless otherwise specified, it allows both constant temperature treatment and treatment within a certain temperature range. The constant temperature treatment allows the temperature to fluctuate within the accuracy range controlled by the instrument.

[0042] The "particles" mentioned in this application, or substances with a defined particle size distribution, do not necessarily have a spherical shape, and may also be irregular. They can be primary particles or secondary particles. The particle size of irregular particles is calculated as the average of their maximum diameter and minimum diameter.

[0043] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions in the embodiments of this application will be described clearly and completely below. For those not specifying specific conditions in the embodiments, they are carried out according to conventional conditions or the conditions recommended by the manufacturer. For reagents or instruments not indicating the manufacturer, they are all conventional products that can be obtained through commercial purchase.

[0044] Example 1: This example provides an aluminum-ion battery, and its preparation process is as follows:

[0045] Synthesis of positive electrode materials: Take a Schlenk storage tube, add 1,3,5-tris(4-formylphenyl)benzene (TFP), 2,6-diaminoanthraquinone (DAAQ), DMAc and mesitylene, and after ultrasonication for 30 seconds, add CH3COOH aqueous solution to the mixture, and seal it after three freeze-pump-thaw cycles. When the temperature returns to room temperature, put it in an oven and heat it at 120°C for 3 days. After precipitation and filtration, it is thoroughly washed with DMF and acetone. After drying at 120°C for 12 hours, a brown powder is obtained, which is a covalent organic framework material, named DAAQ-COF. The specific surface area of DAAQ-COF is 461.97m 2 / g, such as Figure 7 shown.

[0046] Preparation of the positive electrode: Clean the surface of the tantalum foil with alcohol. After the oil stains on the surface of the tantalum foil are cleaned, use a punch to punch it into a 10mm diameter disc for later use. Next, prepare the positive electrode slurry: weigh 5mg of DAAQ-COF and 4mg of graphene, add them to an agate mortar, and grind them for about 30 minutes. At this time, the graphene and active material have been evenly mixed. Then transfer them to a stirring bottle, add 1mg of PVDF binder and an appropriate amount of NMP (N-methylpyrrolidone), and stir them on a magnetic stirrer overnight to obtain a uniform black slurry. Place the previously prepared tantalum sheet on a clean glass plate, and then evenly coat the prepared slurry on the tantalum sheet current collector. Place it in a vacuum drying oven and dry it at 60°C for 6 hours to obtain the prepared positive electrode sheet.

[0047] Battery assembly: In an argon-filled glove box, the prepared positive electrode sheet, glass fiber separator, aluminum negative electrode, and anhydrous aluminum chloride-1-ethyl-3-methylimidazolium chloride ionic liquid electrolyte with a molar ratio of 1.3:1 were assembled into an aluminum ion battery.

[0048] Performance test: Cyclic voltammetry test was performed in the voltage range of 0.8 to 1.9, such as Figure 1 As shown; constant current charge and discharge and cycle performance tests were carried out in the voltage range of 0.8 to 1.9, as shown Figure 2 and Figure 3 shown.

[0049] Example 2: This example provides an aluminum ion battery, the preparation process of which is as follows:

[0050] Synthesis of the positive electrode material: Take a Schlenk storage tube, add 1,3,5-tris(4-formylphenyl)benzene (TFP), 2,7-diamino-9,10-phenanthrenequinone (DAPQ), DMAc and mesitylene. After ultrasonic treatment for 30 seconds, add an aqueous solution of CH3COOH to the mixture, and seal it after three freeze-pump-thaw cycles. When the temperature returns to room temperature, place it in an oven and heat it at 120 °C for 3 days. After the growth of organic crystals is completed, separate by precipitation filtration, and thoroughly wash with DMF and acetone. Then dry at 120 °C for 12 hours to obtain a black powder, which is the covalent organic framework material named DAPQ-COF. The specific surface area of DAPQ-COF is 301m 2 / g, as Figure 8 shown

[0051] Fabrication of the positive electrode plate: Clean the surface of the tantalum foil with alcohol. After the oil stain on the surface of the tantalum foil is cleaned, punch it into a round piece with a diameter of 10 mm for standby. Next, prepare the positive electrode slurry: Weigh 5 mg of DAPQ-COF and 4 mg of graphene, add them to an agate mortar, and grind for about 30 minutes. At this time, the graphene and the active material are evenly mixed, and then transfer them to a stirring bottle, add 1 mg of PVDF binder and an appropriate amount of NMP (N-methylpyrrolidone), and stir overnight on a magnetic stirrer to obtain a uniform black slurry. Place the previously prepared tantalum sheet on a clean glass plate, and then evenly coat the prepared slurry on the tantalum sheet current collector, and place it in a vacuum drying oven. After drying at 60 °C for 6 hours, the prepared positive electrode plate is obtained.

[0052] Assembly of the battery: In a glove box filled with argon, assemble the prepared positive electrode plate, glass fiber separator, aluminum negative electrode, and an aluminum chloride-1-ethyl-3-methylimidazolium chloride ionic liquid electrolyte with a molar ratio of 1.3:1 into an aluminum-ion battery.

[0053] Performance test: Perform cyclic voltammetry tests in the voltage range of 0.8 - 1.9, as Figure 4 shown; perform constant current charge-discharge and cycling performance tests in the voltage range of 0.8 - 1.9, as Figure 5 and Figure 6 shown.

[0054] Example 3: The difference between this example and Example 1 is that in the preparation step of the positive electrode slurry, the addition amount of DAAQ-COF is 7 mg, the addition amount of the conductive agent is 2 mg, the addition amount of the binder is 0.8 mg, and the conductive agent is acetylene black; coat the slurry on the surface of the current collector and dry it under vacuum conditions at 80 °C.

[0055] Example 4: The difference between this example and Example 1 is that the molar ratio of AlCl3 to the ionic liquid in the electrolyte is adjusted to 1.5:1.

[0056] Comparative Example 1: This comparative example provides an aluminum-ion battery, and its preparation process is as follows:

[0057] Fabrication of the positive electrode sheet: Clean the surface of the tantalum foil with alcohol. After the oil stain on the surface of the tantalum foil is cleaned, punch it into a circular sheet with a diameter of 10 mm for standby. Next, prepare the positive electrode slurry: Weigh 5 mg of anthraquinone (AQ) and 4 mg of graphene, add them to an agate mortar, and grind for about 30 minutes. At this time, the graphene and the active material have been evenly mixed, and then transfer them to a stirring bottle, add 1 mg of PVDF binder and an appropriate amount of NMP (N-methylpyrrolidone), and stir overnight on a magnetic stirrer to obtain a uniform black slurry. Place the previously prepared tantalum sheet on a clean glass plate, and then evenly coat the prepared slurry on the tantalum sheet current collector, and put it into a vacuum drying oven. After drying at 60 °C for 6 hours, the prepared positive electrode sheet is obtained.

[0058] Assembly of the battery: In a glove box filled with argon, assemble the prepared positive electrode sheet, glass fiber separator, aluminum negative electrode, and an anhydrous aluminum chloride-1-ethyl-3-methylimidazolium chloride ionic liquid electrolyte with a molar ratio of 1.3:1 into an aluminum-ion battery.

[0059] Comparative Example 2: This comparative example provides an aluminum-ion battery, and its preparation process is as follows:

[0060] Fabrication of the positive electrode sheet: Clean the surface of the tantalum foil with alcohol. After the oil stain on the surface of the tantalum foil is cleaned, punch it into a circular sheet with a diameter of 10 mm for standby. Next, prepare the positive electrode slurry: Weigh 5 mg of phenanthraquinone (PQ) and 4 mg of graphene, add them to an agate mortar, and grind for about 30 minutes. At this time, the graphene and the active material have been evenly mixed, and then transfer them to a stirring bottle, add 1 mg of PVDF binder and an appropriate amount of NMP (N-methylpyrrolidone), and stir overnight on a magnetic stirrer to obtain a uniform black slurry. Place the previously prepared tantalum sheet on a clean glass plate, and then evenly coat the prepared slurry on the tantalum sheet current collector, and put it into a vacuum drying oven. After drying at 60 °C for 6 hours, the prepared positive electrode sheet is obtained.

[0061] Assembly of the battery: In a glove box filled with argon, assemble the prepared positive electrode sheet, glass fiber separator, aluminum negative electrode, and an anhydrous aluminum chloride-1-ethyl-3-methylimidazolium chloride ionic liquid electrolyte with a molar ratio of 1.3:1 into an aluminum-ion battery.

[0062] Table 1: Comparison of the electrochemical performances of Example 1, Example 2, Comparative Example 1, and Comparative Example 2

[0063]

[0064] Please refer to Table 1 and Figures 1-6, From the electrochemical performance tests of Examples 1-4, it can be seen that thanks to the multi-carbonyl active sites, DAAQ-COF can achieve a high specific capacity of about 121 mAh g -1 at a current density of 0.2 Ag-1. At the same time, the strong π-π conjugate framework and porous structure enable DAAQ-COF to still retain a specific aluminum storage capacity of about 81 mAh g -1 at an ultra-high current density of 3 Ag -1 and can retain 93.6% of the initial capacity after 6,000 stable cycles. Although the discharge capacity of DAPQ-COF in Example 2 is slightly lower than that of DAAQ-COF, the discharge voltage platform is increased by about 17% compared to DAAQ-COF, and the energy density is improved. In terms of cycle stability, DAPQ-COF is as excellent as DAAQ-COF. After 6,000 stable cycles at a current density of 2 Ag -1 , the capacity retention rate is as high as 98%.

[0065] Comparing the electrochemical performance tests of Example 1 and Comparative Example 1, it can be seen that due to the relatively large solubility of the monomer small molecule anthraquinone (AQ) in the electrolyte, the cycle performance is significantly worse than that of DAAQ-COF, and at a high rate (3 A / g), the specific capacity is only 22.5 mAh g -1 . Similarly, the cycle stability and rate performance of phenanthraquinone (PQ) in Comparative Example 2 are also significantly worse than those of DAPQ-COF in Example 2. It should be noted that since the solubility of phenanthraquinone (PQ) in the electrolyte is greater than that of anthraquinone (AQ), when the electrode is infiltrated with the electrolyte, the active material will fall off in a large area, resulting in an initial capacity of only 35.2 mAh g -1 . According to Figures 7-8 the data, the specific surface areas of the cathode materials prepared by this scheme are all greater than 300 m 2 / g, especially Example 1 can reach 461.97 m 2 / g.

[0066] In summary, the covalent organic framework material synthesized from 1,3,5-tris(4-formylphenyl)benzene (TFP) and organic active units is a cathode material for aluminum-ion batteries with excellent electrochemical performance and has strong application prospects.

[0067] The technical features of the above embodiments can be combined arbitrarily. For the sake of brevity of description, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, it should be considered as the scope recorded in this specification.

[0068] The above embodiments only represent several implementation manners of the present application. The description thereof is relatively specific and detailed, but it should not be construed as a limitation on the scope of the invention patent. It should be noted that for those of ordinary skill in the art, without departing from the concept of the present application, several modifications and improvements can still be made, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent of the present application shall be subject to the appended claims.

Claims

1. An organic cathode material for an aluminum-ion battery, characterized in that, Comprising the following components by mass parts: Organic active substance, which is a covalent organic framework material synthesized by a solvothermal method from 1,3,5-tris(4-formylphenyl)benzene and a quinone compound with a carbonyl active site. The covalent organic framework material has a porous structure and a π-π conjugated backbone.

2. The organic cathode material for an aluminum ion battery according to claim 1, characterized in that, The X-ray diffraction pattern of the covalent organic framework material has a diffraction peak at 2θ < 5°.

3. The organic cathode material for an aluminum-ion battery according to claim 1, characterized in that, The quinone compound is at least one of 2,6-diaminoanthraquinone, 2,7-diamino-9,10-phenanthrenequinone, and 2,7-diaminopyrene-4,5,9,10-tetrone.

4. The organic cathode material for an aluminum-ion battery according to claim 1, characterized in that, Containing 40 - 70 parts of the organic active substance and 28 - 62 parts of the inactive component.

5. The aluminum-ion battery organic cathode material according to claim 4, characterized in that, Containing 20 - 50 parts of the conductive agent and 8 - 12 parts of the binder.

6. The organic cathode material for an aluminum ion battery according to claim 5, characterized in that, The binder is selected from at least one of polyvinylidene fluoride, sodium carboxymethyl cellulose, sodium alginate, and styrene-butadiene rubber.

7. The aluminum ion battery according to claim 1, characterized in that, The specific surface area of the organic cathode material is greater than 300 m 2 / g.

8. An aluminum-ion battery, characterized in that, Including: a) A positive electrode prepared by coating the organic positive electrode material according to any one of claims 1 - 7 on a conductive current collector; b) A negative electrode, which is a metal foil; c) A separator, which is an insulating material separator; d) An electrolyte.

9. The aluminum ion battery according to claim 8, characterized in that, The preparation method of the positive electrode includes the following steps: a) Mix the organic active substance, the conductive agent, and the binder according to mass parts, and add a solvent and stir until the slurry is uniform; b) Coat the slurry on the surface of the current collector and dry it under vacuum conditions at 60 - 80 °C; c) Cut the dried electrode sheet into a preset size.

10. The aluminum ion battery according to claim 8, wherein, The electrolyte is a room temperature ionic liquid composed of anhydrous AlCl3 and 1-ethyl-3-methylimidazolium chloride in a molar ratio of (1.2 - 1.5):1.